Protective and therapeutic potentials of HDL and ApoA1 in COVID-19 elderly and chronic illness patients - AbdelHafez, Mohamed Aly (2023)
HDL has multiple physiological functions; i.e. reverse cholesterol transport, anti-inflammatory, anti-thrombotic, anti-oxidative, anti-apoptotic in addition to protection of vascular endothelium against damage and leakage of small particles like LDL to pass through. Apo-lipoprotein A1 (Apo-A1) is the main apo-lipoprotein component and plays an axial role in HDL function. Alterations of HDL disturb its functions. Elderly subjects, obese patiens, and patients with chronic illness such as diabetes, cardiovascular disease (CVD) or chronic inflammatory diseases have bad comorbidity among COVID19 patients. Inflammation affect HDL structure and function. COVID-19 causes systemic immune-inflammation due to cytokine explosion, viral interaction with erythrocytes and its hemoglobin content and other factors influencing HDL function. Clinical and experimental trials suggest that resuming the HDL function by administration of reconstituted HDL, Apo-A1 mimetic peptide D-4F, ω-3 polyunsaturated fatty acids, and/or the powdered roots of Saussurea costus ameliorates the clinical outcome. We recommend application of these to regain HDL protective function in the fore-mentioned cases.